Polypill for atherosclerotic cardiovascular disease prevention in Haiti: Eligibility estimates in a low-income country - Yan, Lily D.; Rouzier, Vanessa; Pierre, Jean Lookens; Dade, Eliezer; Sufra, Rodney; Huffman, Mark D.; Apollon, Alexandra; St Preux, Stephano; Metz, Miranda; Sabwa, Shalom; Morisset, Béatrice; Deschamps, Marie; et al. (Frontiers in Epidemiology, 2022)
Background Multidrug therapy is a World Health Organization “best buy” for the prevention and control of noncommunicable diseases. CVD polypills, including ≥2 blood pressure medications, and a statin with or without aspirin, are an effective, scalable strategy to close the treatment gap that exists in many low- and middle-income countries, including Haiti. We estimated the number of Haitian adults eligible for an atherosclerotic CVD (ASCVD) polypill, and the number of potentially preventable CVD events if polypills were implemented nationally. Methods We used cross-sectional data from the Haiti CVD Cohort, a population-based cohort of 3,005 adults ≥18 years in Port-au-Prince, to compare two polypill implementation strategies: high-risk primary prevention and secondary prevention. High-risk primary prevention included three scenarios: (a) age ≥40 years, (b) hypertension, or (c) predicted 10-year ASCVD risk ≥7.5%. Secondary prevention eligibility included history of stroke or myocardial infarction. We then used the 2019 Global Burden of Disease database and published polypill trials to estimate preventable CVD events, defined as nonfatal MI, nonfatal stroke, and cardiovascular death over a 5-year timeline. Results Among 2,880 participants, the proportion of eligible adults for primary prevention were: 51.6% for age, 32.5% for hypertension, 19.3% for high ASCVD risk, and 5.8% for secondary prevention. Based on current trends, an estimated 462,509 CVD events (95% CI: 369,089–578,475) would occur among adults ≥40 years in Haiti from 2019–2024. Compared with no polypill therapy, we found 32% or 148,003 CVD events (95% CI: 70,126–248,744) could be prevented by a combined primary and secondary prevention approach in Haiti if polypills were fully implemented over 5 years. Conclusion These modeling estimates underscore the potential magnitude of preventable CVD events in low-income settings like Haiti. Model calibration using observed CVD events, costs, and implementation assumptions are future directions. Clinical trial registration clinicaltrials.gov, identifier: NCT03892265.